The Fish Fauna in Lakitan River, Musi Rawas Regency, South Sumatra - Dian Samitra; Zico Fakhrur Rozi (UIN Sunan Gunung Djati Bandung, 2019)
Fish diversity in the Lakitan River is not well recorded, even though the data is important to add information about the diversity of freshwater fish in Indonesia. This study aims to study fish composition and ecological index in the Lakitan River. The study was conducted in the Lakitan River, Musi Rawas Regency, South Sumatra Province. The method used was the survey method. The direct sampling was done at 5 stations, the numbering of stations followed the direction of the river from upstream to downstream. The data at each station are tabulated based on species, family and order. Data analysis in-cludes a diversity index, evenness index, dominance index, and sim-ilarity index. The fish caught during the study were 418 individuals, which were identified into 20 species and 11 families. Barbonymus gonionotus is the most captured species in the Lakitan River. Cypri-nidae is the most captured family (9 species). The highest diversity index was found at station 5, with the number of fish collected was 16 species. The evenness index at 5 stations showed the equivalent species distribution and stable communities. The domination index at 5 stations were at, low category. The similarity index between sta-tions in Lakitan River which ranging from 0.65 – 0.97. These results indicate that fish diversity in the Lakitan River medium biodiversity.